Effect of beam shape and spatial energy distribution on weld bead geometry in conduction welding - Suder, Wojciech (Cranfield University, 2019)
Data used in the corresponding paper (link below).
Keywords: 'beam diameter'; 'conduction welds'; 'distortion of spot size'; 'weldbead profile geometry'; 'intensity distribution'; 'Manufacturing Processes and Technologies (excl. Textiles)'